Characteristics of myeloproliferative neoplasms in patients exposed to ionizing radiation following the Chernobyl nuclear accident. Issue 1 (31st October 2018) - Poluben, Larysa; Puligandla, Maneka; Neuberg, Donna; Bryke, Christine R.; Hsu, Yahsuan; Shumeiko, Oleksandr; Yuan, Xin; Voznesensky, Olga; Pihan, German; Adam, Miriam; Fraenkel, Ernest; Rasnic, Roni; et al.
Abstract: Myeloproliferative neoplasms (MPNs) driver mutations are usually found in JAK2, MPL, and CALR genes; however, 10%‐15% of cases are triple negative (TN). A previous study showed lower rate of JAK2 V617F in primary myelofibrosis patients exposed to low doses of ionizing radiation (IR) from Chernobyl accident. To examine distinct driver mutations, we enrolled 281 Ukrainian IR‐exposed and unexposed MPN patients. Genomic DNA was obtained from peripheral blood leukocytes. JAK2 V617F, MPL W515, types 1‐ and 2‐like CALR mutations were identified by Sanger Sequencing and real time polymerase chain reaction. Chromosomal alterations were assessed by oligo‐SNP microarray platform. Additional genetic variants were identified by whole exome and targeted sequencing. Statistical significance was evaluated by Fisher's exact test and Wilcoxon's rank sum test (R, version 3.4.2). IR‐exposed MPN patients exhibited a different genetic profile vs unexposed: lower rate of JAK2 V617F (58.4% vs 75.4%, P = .0077), higher rate of type 1‐like CALR mutation (12.2% vs 3.1%, P = .0056), higher rate of TN cases (27.8% vs 16.2%, P = .0366), higher rate of potentially pathogenic sequence variants (mean numbers: 4.8 vs 3.1, P = .0242). Furthermore, we identified several potential drivers specific to IR‐exposed TN MPN patients: ATM p.S1691R with copy‐neutral loss of heterozygosity at 11q; EZH2 p.D659G at 7q and SUZ12 p.V71 M at 17q with copy number loss. Thus, IR‐exposed MPN patients represent a group with distinct genomic characteristics worthy of further study.